(untitled) (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
This article examines Bogdan Popa’s interpretation of Margaret Canovan’s analysis of the nation as a neglected yet indispensable concept in liberal political theory. It explores the argument that liberalism implicitly relies on national identity while often denying its normative significance, highlighting the tensions between universal political principles and the enduring realities of the nation-state. The article further reflects on the relationship between nation, people, nationalism, and democracy, emphasizing the conceptual and political challenges posed by contemporary debates on identity, populism, and globalization. This abstract is generated with artificial intelligence.